Patrol Observation of the Southern Dwarf Novae at The Bosscha Observatory - Chatief Kunjaya (Institut Teknologi Bandung, 2000)
STUDI APLIKASI METODE POTENSIOMETRI PADA PENENTUAN KANDUNGAN KARBON ORGANIK TOTAL TANAH Â The result of patrol observation of dwarf novae at the Bosscha Observatory are presented. The images of the region of four dwarf novae, MM Scorpii, V2051 Ophiuci, V391 Scuti and V3462 Sagitarii could be taken. MM Scorpii and V391 Scuti were not detectable implying quiescence state. The eclipsing SU UMa type dwarf nova, V2051 Ophiuci was observed during its outburst. Brightness measurement using aperture photometry method yields (15.2 Â± 0.3) mag. V3462 Sagitarii were also detectable and the brightness (15.3 Â± 0.6) mag were derived. Therefore this star is suspected in its outburst state during the observation.